Northern experience and the myths of Canadian culture - Hulan, Renée (McGill-Queen's native and northern series, 2002)
"In Northern Experience and the Myths of Canadian Culture Renee Hulan disputes the notion that the north is a source of distinct collective identity for Canadians. Through a synthesis of critical, historical, and theoretical approaches to northern subjects in literary studies, she challenges the epistemology used to support this idea." "By investigating mutually dependent categories of identity in literature that depicts northern peoples and places, Hulan provides a descriptive account of representative genres in which the north figures as a central theme - including autobiography, adventure narrative, ethnography, fiction, poetry, and travel writing. She considers each of these diverse genres in terms of the way it explains the cultural identity of a nation formed from the settlement of immigrant peoples on the lands of dispossessed indigenous peoples. Reading against the background of contemporary ethnographic, literary, and cultural theory, Hulan maintains that the collective Canadian identity idealized in many works representing the north does not occur naturally but is artificially constructed in terms of characteristics inflected by historically contingent ideas of gender and race, such as self-sufficiency, independence, and endurance, and that these characteristics are evoked to justify the nationhood of the Canadian state."--Jacket.